Peran Service Quality dan Relationship Marketing terhadap Loyalitas Nasabah dengan Kepuasan Nasabah sebagai Variabel Intervening - Afdhilah Rahmah Rini; Irmayanti Hasan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the role of service quality and relationship marketing on customer loyalty and customer satisfaction as an intervening variable at BMT Mandirir Sejahtera, Kranji Paciran Lamongan Branch. With a quantitative approach. Testing this hypothesis uses the Smart PLS test tool. The data in this study by distributing questionnaires to customers of BMT Mandiri Sejahtera Kranji Paciran Lamongan Branch. The results showed that there was an influence between service quality on customer satisfaction, relationship marketing had an effect on customer satisfaction, service quality had an effect on customer loyalty, relationship marketing had an effect on customer loyalty, customer satisfaction had an influence on customer loyalty, service quality had an influence on customer loyalty mediated by customer satisfaction, relationship marketing has an influence on customer loyalty which is mediated by customer satisfaction at BMT Mandiri Sejahtera Kranji Paciran Lamongan Branch. Keywords : Service Quality, Relationship Marketing, Customer Loyalty, Customer Satisfaction